Effect of sonic irrigation activation at different frequencies in smear layer removal; An in vitro experimental study - Eiman Aalmohamed; Fatemeh Ahmed; Layal Alfardan; Rashid El Abed; Amar Hasan Khamis; Mohamed Jamal (Wolters Kluwer Medknow Publications, 2022)
Introduction: The aim of this study was to compare the vibration/oscillation frequencies of WaterPik and EndoActivator devices and their effectiveness in smear layer (SL) removal. Materials and Methods: The root canal of 60 single-rooted extracted human premolars were prepared until ProTaper Universal F2 file, and randomly grouped according to the irrigation activation technique used: EndoActivator group; WaterPik group; manual dynamic agitation (MDA) group; and control group (conventional irrigation with no activation). The vibration/oscillation frequencies of EndoActivator and WaterPik devices were measured using a digital tachometer. Electron microscopy images of all specimens were evaluated for SL removal according to a modified Hülsmann scoring system. Data were statistically analyzed. Results: The mean vibration frequency of the EndoActivator was significantly higher than that of WaterPik (200.6 ± 2.1 and 185.2 ± 2.744 Hz, respectively). A significant difference was detected in the SL removal along the full length of the canal between the experimental and control groups (P < 0.001). EndoActivator and MDA groups had significantly more samples with no to minimum SL at the coronal and middle thirds compared to the apical third, whereas there was no significant difference among the thirds in the WaterPik group. At the apical third, the WaterPik group had significantly more samples with no to minimum SL (60%) than WaterPik and MDA groups (20% and 26.7%, respectively). Conclusion: WaterPik was as effective as MDA and EndoActivator in SL removal, with better performance at the apical third, probably attributed to the lower vibration/oscillation frequency of WaterPik.